Design and analysis of novel 2R1T generalized parallel mechanisms with large rotational angles. (August 2020) - Wang, Lin; Fang, Yuefa; Qu, Haibo; Li, Luquan
Highlights: A synthesis method for 2R1T GPMs with large rotational angles is proposed. Novel 2R1T GPMs with large rotational angles are constructed. Rotational capability analysis of 2R1T GPMs are presented. The rotation angles around the x -axis and y -axis are about −155° to 170° and −160° to 175°. Abstract: Limited rotational angles caused by the interference between the moving platform and kinematic chains of parallel mechanisms (PMs) has always been an issue. Hence a class of two-rotation and one-translation (2R1T) generalized parallel mechanisms (GPMs) with a high rotational capability, where the end effector is placed on the joint to avoid the problem, is presented. This type of GPM consists a multiple joint element and binary links connected by kinematic pairs. Hence the GPM can offer advantages in terms of a simple structure, high machining accuracy, and low machining cost. By combining the Grubler criterion and Euler's equation, the acceptable number of links and kinematic pairs is derived. Depending on the number synthesis results, joint arrangements are considered in each kinematic chain. Then the structure of kinematic chains is synthesized by virtual work. Examples of the 2R1T GPMs constructed by enumerated chains are shown. Finally, a kinematic analysis is performed on an example. The rotational performance and the singularity conditions are investigated. According to the above analyses, the rotational performance of 2R1T GPMs is excellent.